P-B30 Association between HIV and persistent HPV infections among Nigerian women. (January 2016) - Adebamowo, Sally; Famooto, Ayo; Dareng, Eileen; Olawande, Toyosi; Offiong, Richard; Olaniyan, Olayinka; Adebamowo, Clement
Abstract : Background: Cervical cancer incidence has remained stable in HIV+ women but the prevalence, persistence and multiplicity of HPV infection appears different comparing HIV+ to HIV− women. We examined the association between HIV, prevalent and persistent HPV infections among women in a prospective cohort in Nigeria. Methods: Women were recruited from cervical cancer screening programs in Abuja, Nigeria between 2012 and 2014, data on demographic characteristics, risk factors of HPV infection and samples of cervical exfoliated cells were collected at baseline, 6 and 12 months follow-up visits. DNA enzyme immunoassay (DEIA) and Roche Linear Array HPV Genotyping Test were used to characterize HPV. Persistent HPV infection was defined as positive results on 2 consecutive DEIA tests. Logistic regression models were used to estimate the association between HIV and the risk of HPV infections. Results: Among the 1020 women enrolled, the mean age (±SD) was 37 (8), 44% and 56% were HIV+ and HIV-, respectively. The prevalence of any HPV infection was 53% (58% among HIV+; 42% among HIV−, P -value <0.001); the prevalence of persistent HPV infection was 17% (78% among HIV+; 22% among HIV−, P -value <0.001). The multivariate relative risk and 95% confidence interval (95% CI) was 3.22 (95% CI: 2.40 to 4.32, P -value <0.001) for any HPV infection and 5.52 (95% CI: 3.61 to 8.44, P -value <0.001) for persistent HPV infection, comparing HIV+ to HIV− women, adjusted for variables that reached statistical significance in univariate analyses: age, age at sexual initiation, number of lifetime sexual partners, marital status and level of education. Conclusions: HIV infection is associated with increased risk of any HPV and persistent HPV infections. Previously, we reported that the most prevalent high risk HPV types were HPV35 (8.7%) and HPV56 (7.4%) among HIV+ women, and HPV52 and HPV68 (2.8%, each) among HIV- women, from a subset of this population. We will present the results of the specific HPV types in the entire study population, at the forthcoming conference.